Convenient Stereoselective Synthesis of Substituted Ureido Glycosides Using Stable 4-Chlorophenylcarbamates without the Requirement of Lewis Acids - van der Wal, Steffen; Fu, Ou; Rontogianni, Stamatia; Pieters, Roland J.; Liskamp, Rob M. J. (Synlett, 2014)
A modification of the synthesis of substituted ureido glycosides in a stereospecific fashion is described, in which commercially available azido glycosides are reduced to the amines, which are then reacted with 4-chlorophenyl chloroformate to the corresponding 4-chlorophenyl carbamate of the glycosides. These synthetic intermediates are stable at room temperature and have a long shelf life, and can transiently form the 1-isocyanato glycosides under mildly basic conditions, which subsequently can react with amines to form substituted ureido glycosides
Keywords: carbohydrates; stereoselective synthesis; azides; urea; carbamates